2022
DOI: 10.3991/ijim.v16i09.28289
|View full text |Cite
|
Sign up to set email alerts
|

A Social Virtual Reality Mobile Application for Learning and Practicing English

Abstract: Many studies promise that virtual reality (VR) applications will be one of the most used tools in foreign language learning. This is because VR keeps learners engaged, motivated, and prepared with better communication skills due to the simulation of real-life environments. As a result of the COVID-19 pandemic and social distancing, it became difficult to use and practice newly learned language skills with real people directly. This paper proposes a social VR mobile application that can be used anytime anywhere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 35 publications
3
12
0
Order By: Relevance
“…The authors fully agree with the researchers who analysed the benefits of different Apps for learning English [34], [36], [37]. Moreover, we have verified the evidence of some apps efficacy for developing reading and comprehension skills and use of English skills.…”
Section: Discussion and Limitationsupporting
confidence: 80%
See 3 more Smart Citations
“…The authors fully agree with the researchers who analysed the benefits of different Apps for learning English [34], [36], [37]. Moreover, we have verified the evidence of some apps efficacy for developing reading and comprehension skills and use of English skills.…”
Section: Discussion and Limitationsupporting
confidence: 80%
“…Thus, the mentioned signifies that mobile learning applied in the experimental group was more efficient according to the students' results during "Legal English" than traditional learning, which was utilised in the control group. The obtained results of our experiment do not contradict the research findings of Zhang [34], Klimova [35] and Alwafi et al [36], who investigated mobile learning technology is a complementary method of teaching and learning English.…”
Section: Fig 1 Comparison Diagram Of Students' Academic Performancesupporting
confidence: 73%
See 2 more Smart Citations
“…Over the last decade, a number of studies have shown that these virtual tools and platforms can greatly enhance learning experiences [6][7][8][9][10][11][12][13][14]. It has also been used during the pandemic to aid language learners during the lockdown, with no possibility of practicing their speaking skills in the real world [15]. Moreover, they have been used to teach learners with special needs how to deal with issues both in and out of the classroom.…”
Section: Introductionmentioning
confidence: 99%